Sales Contract in Islamic Finance: A Comparative Analysis - Jusoh, Dr. Hashim; Baba, Zaharah Salwati; Taha, Ahmad Tirmizi; Ismail, Dr. Ahmad Faizol; Abdul Razak, Dr. Roslida (Penerbit UniSZA, 2016)
Islamic sales contract plays a vital role and contribute significantly in Islamic commercial law or fiqh muamalat. In Malaysia,the principle of bay al-dayn trading is being accepted as one of the concepts for developing Islamic capital market instrument. However, the application of the concept is argued among past and present Islamic jurists.The aim of this chapter is that the application of bay al-dayn which one of the Shariah compliance Islamic Banking and financing instruments has positively applied in Malaysia. Therefore, this chapter provides deeper understanding of the hidden transformation of sales contract using the principle of bay al-dayn regardless classical and contemporary views of scholar.